Aplikasi Pupuk Organik Cair dari Limbah Pasar pada Tanaman sawi (Brasica juncea L.) - Murdaningsih Murdaningsih; Philipus Nerius Supardi; Yoseph Peke (AGRICA, 2020)
Research on Application of Liquid Organic Fertilizer from Market Waste in Chinese Mustard Plants (Brasica juncea L.). The production of mustard greens in Ende Regency is still low compared to the production of mustard greens. This condition is caused by fertilization that has not been optimal. Efforts to increase mustard production through the application of technology, especially the use of fertilizers, including using liquid organic fertilizer Market waste that can provide nutrients for plants.This study aims to determine the application dose of liquid organic fertilizer from market waste and the response of growth and yield of mustard plants. The study was conducted in the experimental garden of the Faculty of Agriculture, University of Flores in Ende, using a Randomized Block Design consisting of five treatments using Liquid organic fertilizer (POC) from Market Waste namely L0 (without POC), L1 (10 liters of POC), L2 (20 liters POC), L3 (30 liters of POC), L4 (40 liters of POC), repeated four times. The results showed that the application of POC from market waste significantly affected plant height, number of leaves, fresh weight of mustard greens, fresh weight of mustard ha-1 and dose of 40 liters ha-1 showed the best growth, which was an average plant height of 24.68 cm, number of leaves 9.25 strands, fresh weight of mustard 147.40 g and production of mustard 23.58 tons ha-1